Using Diaries to Promote Reflection on Teaching - Hull, Jonathan (rEFLections, 2007)
This diary study reports on an experienced teacher’s reflections on his teaching of two classes, one undergraduate and the other graduate, over half a semester. The data were subjected both to content analysis and keyword analysis, the latter to mitigate to some extent the effects of subjectivity. Issues found for the undergraduate class include the role of task type in motivating students to use English during group work, the amount of time expended on the pre-teaching of vocabulary and, related, a tendency to teacher-centredness; in contrast, in the graduate class, there was extensive evidence of teacher digression from lesson plans.